EFFECTS OF INUNDATION DEPTH ON GROWTH OF 14 PLANT SPECIES ON PEATLANDS IN PULANG PISAU REGENCY - Rotinsulu, Johanna M.; Indrayanti, Lies; Sampang, Sampang (TROPICAL WETLAND JOURNAL, 2016)
Rehabilitation of degraded peat-swamp forests, especially in Central Kalimantan Province, is becoming increasingly important in order to restore the ecological functions and maintain the biodiversity and carbon pool. The problem facing the rehabilitation effort is the limited knowledge about the techniques of rehabilitation on peat swamp lands using local species because inundation frequently occurs in this area during rainy season which greatly affects the growth of the plants. The purpose of this study was to analyze the level of resistance of plants to inundation on peat swamp lands in Pulang Pisau Regency, Central Kalimantan Province. The experiment was conducted in Taruna Jaya village, Jabiren subdistrict. Pulang Pisau Regency, using 14 different plant species endemic to peat swamp forests, with two factors, namely the level of immersion/inundation and plant species. In order to find out the plant resistance to inundation and the root growth, some variables were measured, such as the survival percentage of plants after tested in inundation and planted in the field, the assessment of the tree health using the criteria of Forest Health Monitoring (FHM), and the root-shoot ratio (RSR). The results showed that of the 14 species tested, Belangeran (Shorea balangera Korth) and Bintangur (Calophylum sp.) had good resistance to the condition of inundated soil, high adaptability in the field, and high value of RSR (root- shoot ratio). The plant species with high efficiency in absorbing nutrients and water were Shorea balangeran Korth, Calophyllum sp., Dyera polyphylla, and Alstonia pneumatophora. Those with the very high value of tree health were Alstonia pneumatophora, Calophyllum sp., D. pseudomalabarica, Dyera polyphylla, Shorea balangeran Korth, Trisraniopsis sp. and Stemonurus secondflorus.